2006
DOI: 10.1161/01.hyp.0000217972.80731.ef
|View full text |Cite
|
Sign up to set email alerts
|

Do Allelic Variants in α 2A and α 2C Adrenergic Receptors Predispose to Hypertension in Blacks?

Abstract: Abstract-Sequence variations in the human ␣ 2 adrenergic receptor genes (ADRA2A and ADRA2C) have been implicated as a cause of hypertension in blacks. Although certain alleles are selectively enriched in blacks, their association with hypertension is based on small convenience samples and has not been evaluated in larger populations. From a stratified random population sample of 3398 individuals (52% blacks), we obtained DNA samples together with an in-home health interview, 10 in-home measurements of blood pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
21
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 28 publications
6
21
1
1
Order By: Relevance
“…5 However, larger studies found no associations between the ADRA2C deletion and markers of elevated resting sympathetic tone, blood pressure, or heart rate. 10,22 Variable results regarding the association between the ADRA2C deletion variant and cardiac function 14,23 suggest that the functional effects of the deletion variant may be most apparent in circumstances of substantially elevated sympathetic tone (eg, after yohimbine administration or in advanced congestive heart failure), and only in subjects who are homozygous for the deletion. 10,24 Another approach to examine the functional consequences of the ADRA2C deletion is to administer an ␣ 2 -AR agonist.…”
Section: Discussionmentioning
confidence: 99%
“…5 However, larger studies found no associations between the ADRA2C deletion and markers of elevated resting sympathetic tone, blood pressure, or heart rate. 10,22 Variable results regarding the association between the ADRA2C deletion variant and cardiac function 14,23 suggest that the functional effects of the deletion variant may be most apparent in circumstances of substantially elevated sympathetic tone (eg, after yohimbine administration or in advanced congestive heart failure), and only in subjects who are homozygous for the deletion. 10,24 Another approach to examine the functional consequences of the ADRA2C deletion is to administer an ␣ 2 -AR agonist.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence variations in the human α -2 adrenoreceptor genes have been implicated as a cause of hypertension in African Americans. A study of adrenoreceptor genes (ADRA2A and ADRA2C) from the Dallas Heart Study did not fi nd an association with hypertension in African Americans despite evidence of selective enrichment of these alleles in African Americans [ 42 ]. Renal cytochrome P450 3A5 (CYP3A5) activity has been associated with blood pressure and salt sensitivity in humans.…”
Section: Geneticsmentioning
confidence: 99%
“…These two pieces of evidence illustrate the variability in conclusions commonly seen among different genetic association studies. The largest association study for a 2 ARs and hypertension carried out to date by Li, Canham, Vongpatanasin, Leonard, Auchus, and Victor (2006) revealed negative results for both the a 2A AR DraI RFLP and a 2C AR Del322-325 variant and associations with hypertension and parameters of hypertensive heart disease. Other a 2A AR polymorphisms have been studied in the context of hypertension, with no association found between a novel Bsu361 RFLP and hypertension in a Japanese population (Umemura et al, 1994).…”
Section: B Hypertensionmentioning
confidence: 97%